Chapter 7 Aptamer-Nanoparticle Bioconjugates for Drug Delivery - Schäfer, Thomas (InTechOpen, 2012)
Drug delivery systems traditionally relied on passive diffusion mechanisms for targeting and releasing of therapeutically active molecules. The major problems associated with traditional delivery are poor specificity and dose-limited toxicity. Nanoparticles have found applicability in the development of novel drug delivery systems by easily overcoming toxicity problem. However, specificity of delivery has remained as a challenge. Developments in the methods of reaching to targeted tissue have lead to new and improved drug delivery platforms. Recently, active targeting has been incorporated by cell specific ligands such as antibodies, lectins, growth factor receptors. More recently, aptamers gained popularity in construction of novel actively targeted drug delivery systems (Ozalp et al., 2011). Considerable proportions of aptamer-based delivery systems have been incorporated to a variety of nanomaterials in order to improve their specific targeting properties (Chen et al., 2011; Zhou et al., 2011).